Cerebral Palsy—Trends in Epidemiology and Recent Development in Prenatal Mechanisms of Disease, Treatment, and Prevention - Stavsky, Moshe; Mor, Omer; Mastrolia, Salvatore Andrea; Greenbaum, Shirley; Than, Nandor Gabor; Erez, Offer (Frontiers in Pediatrics, 2017)
Cerebral palsy (CP) is the most common motor disability in childhood. This syndrome is the manifestation of intrauterine pathologies, intrapartum complications and post-natal sequel, especially among preterm neonates. A double hit model theory is proposed suggesting that an intrauterine condition along with intrapartum or postnatal insult lead to the development of CP. Recent reports demonstrated that treatment during the process of preterm birth like magnesium sulfate and post-natal modalities such as cooling may prevent or reduce the prevalence of this syndrome. Moreover, animal model demonstrated that post-natal treatment with anti-inflammatory drugs coupled with nanoparticles may affect the course of the disease in pups with neuroinflammation. The current review would describe the changes in the epidemiology of this disease, the underlying prenatal mechanisms, and possible treatments that may reduce the prevalence of CP and alter the course of disease.